Экологические проблемы методов добычи сланцевого газа в Харьковской области - Гринь, Светлана Александровна; Босюк, Алена Сергеевна; Лаптий, Ольга Александровна (НТУ "ХПИ", 2017)
Рассматриваются экологические проблемы методов добычи сланцевого газа в Харьковской области. Для выявления проблем было рассмотрено виды добычи газа на Слобожанщине и в странах с развитой экономикой. Фрекинг имеет ряд недостатков: загрязнение подземных горизонтов, воздействие на поверхностные водоемы, сейсмические риски, выбросы. В ходе исследования и сравнительного анализа методов извлечения залежей сланцевого газа, установлено ряд преимуществ инновационных и модернизированных способов над методом гидроразрыва пласта. Были предложены пути решения выявленных проблем, которые заключаются в оптимизации процессов добычи.

The ecological problems of the methods of extraction of shale gas in the Kharkov region are considered. To identify problems, the types of gas production in Slobozhanshchina and in advanced economies were considered. Frecking has a number of shortcomings: pollution of underground horizons, impact on surface water bodies, seismic risks, emissions. In the course of the study and a comparative analysis of the methods of extraction of shale gas deposits, a number of advantages of innovative and modernized methods over the hydraulic fracturing method have been established. Ways were proposed to solve the identified problems, which are to optimize the production processes. Ecological problems of methods of extraction of shale gas in the Kharkov region consist in: pollution of underground horizons, impact on surface water bodies, seismic risks, emissions.
Ecological problems of methods of extraction of shale gas in the Kharkov region
Keywords: фрекинг; гидроразрыв пласта; окружающая природная среда; плея; недра; frecking; surrounding natural environment